Cell-Free Transcription of Mammalian Chromatin: Transcription of Globin Messenger RNA Sequences from Bone-Marrow Chromatin with Mammalian RNA Polymerase - Steggles, A. W. (1974)
A mammalian cell-free transcriptional system was developed in which mammalian RNA polymerase synthesizes globin messenger RNA sequences from bone-marrow chromatin. The messenger RNA sequences are detected by measurement of the ability of the transcribed RNA to hybridize with globin complementary DNA. The globin complementary DNA is synthesized by the enzyme from avian myeloblastosis virus, RNA-directed DNA polymerase, with purified globin messenger RNA as template. The specificity of the globin complementary DNA in annealing reactions was verified by preparing DNA complementary to liver messenger RNA and showing that the globin and liver complementary DNAs are specific for their own messenger RNAs. Both DNA-dependent RNA polymerase II from sheep liver and RNA polymerase from Escherichia coli can transcribe globin messenger RNA sequences from rabbit bone-marrow chromatin; however, the mammalian enzyme appears to be more specific in that globin gene sequences represent a higher proportion of the RNA synthesized. Neither polymerase can transcribe globin messenger RNA sequences from rabbit-liver chromatin. This cell-free assay system should be useful in searching for mammalian transcriptional regulatory factors.